Proceedings on Intelligent Systems and Knowledge Engineering (ISKE2007) 2007
DOI: 10.2991/iske.2007.111
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evaluation Model with Unbalanced Linguistic Information

Abstract: The evaluation processes are used for quality inspection, marketing and other fields in industrial companies. This contribution focuses in sensory evaluation where the evaluated items are assessed according to the knowledge acquired via human senses by a panel of experts. In these evaluation processes the information provided by the experts implies uncertainty, vagueness and imprecision. The use of the Fuzzy Linguistic Approach [1] has provided successful results modeling such a type of information. Usually ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Step I-4. Obtain the overall group aggregation results of each alternative r j ( j = 1, 2, 3, 4) by Equation (28). For brevity, the details of r j ( j = 1, 2, 3, 4) are omitted here.…”
Section: Case Study On Governmental Website Usability Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Step I-4. Obtain the overall group aggregation results of each alternative r j ( j = 1, 2, 3, 4) by Equation (28). For brevity, the details of r j ( j = 1, 2, 3, 4) are omitted here.…”
Section: Case Study On Governmental Website Usability Evaluationmentioning
confidence: 99%
“…However, when it comes to more complicated MAGDM problems, where problem structures are ill-defined for fuzzy quantification, Zadeh [25] has advocated the usage of linguistic variables for decision makers to qualitatively express their uncertain preferences. To this end, because of the merit in eliciting decision maker assessments more directly and precisely, linguistic variables have been continuously extended to accommodate various scenarios, such as unbalanced linguistic variables [26][27][28][29], uncertain linguistic variables [30][31][32][33], intuitionistic uncertain variables [34,35], hesitant fuzzy uncertain linguistic variables [15], and hesitant fuzzy unbalanced linguistic variables [36], among others. Although the above extensions of linguistic variables are very effective in situations where decision makers can approximate the most precise linguistic label in accordance with their assessment, Rodríguez et al [37] revealed that decision makers are often cognitively irresolute among several possible linguistic labels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although researches in both contractor selection literature and MADM literature have presented rich approaches for application to green contractor selection problems, there is still a gap with three facets to be further investigated concurrently. First, most of existing hesitant fuzzy linguistic expression tools were based on rigidly uniform or symmetrical linguistic label sets [55,56]; however, practical studies [57,58] have revealed that decision-makers are inclined to express their complicate assessments more precisely and objectively by use of non-uniform or asymmetric linguistic term set, that is, the unbalanced linguistic term set (ULTS) [59]. Second, under complicate decision-making environments, interdependency among attributes is a serious issue that needs to be addressed [60].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cabrerizo et al 6,7 presented a consensus-based group decision making with unbalanced linguistic terms. Martínez et al 32 applied the model with unbalanced linguistic terms to sensory evaluation. Herrera-Viedma and López-Herrera 28 developed a model of information retrieval system with unbalanced fuzzy linguistic information.…”
Section: Introductionmentioning
confidence: 99%